Hepáticas y Antocerotas (Marchantiopsida y Anthocerotopsida) de Salamanca (España). - Elías Rivas, María Jesús; Sánchez, J.A.; García, J.M. (Botanica Complutensis, 2001)
ELÍAS RIVAS, M. J., SÁNCHEZ RODRÍGUEZ, J. A. & GARCÍA DE LAS HERAS, J. M. 2001. Liverworts and Hornworts (Marchantiopsida. and Anthocerotopsida) of Salamanca (Spain). Bot Complutensis 25: 207-212. In this work, the provincial Anthocerotopsida and Marchantiopsida catalogue of Salamanca is given. We have compiled data from known bibliography until today and as a result of this, there are 95 dated taxa. We have also added 3 new data: Riccia subbifurca, R. sorocarpa and R. cavernosa, so that the number of provincial known taxa goes to 98.
Keywords: Liverworts; Hornworts; checklist; Salamanca